Non-Inferiority of Point-of-Care Ultrasound Compared to Radiography to Diagnose Upper Extremity Fractures in Children - David Troxler; Carlos Sanchez; Thierry de Trey; Johannes Mayr; Michael Walther (MDPI AG, 2022)
Conventional X-ray imaging for fracture diagnosis is time-consuming and exposes patients to ionizing radiation. Additionally, the positioning of the injured limb for standardized X-ray imaging is painful. Point-of-care ultrasound (POCUS) is increasingly available in medical offices and emergency rooms. This study aimed to prove the non-inferiority of POCUS compared to X-ray imaging with respect to diagnostic sensitivity, pain, and investigation time in the diagnosis of long-bone fractures of the upper extremity in children. Children and adolescents (1-18 years old) presenting to the UKBB emergency service between May 2020 and May 2021 with suspected upper extremity fracture were included in the study. Before obtaining X-ray images, we conducted a POCUS examination of the injured limb. Pain scores at inclusion as well as maximum pain scores during X-ray and ultrasound examinations were documented. The duration of POCUS and X-ray examinations was compared. We examined 403 children with POCUS and plain X-ray imaging. The mean age (±SD) of the children was 10.6 (±3.5) years. The non-inferiority of POCUS compared to X-ray was confirmed with an estimated sensitivity of 0.95 and a lower confidence interval of 0.93. Maximum pain during POCUS was significantly lower compared to pain at inclusion (p = 0.002) or maximum pain during radiographic examination (p = 0.03). POCUS examination took 3.9 (±2.9) min in the mean whilst the mean duration for obtaining the X-ray images was 16 (±37) min (p < 0.001). POCUS for diagnosing upper extremity fractures in children proved as sensitive as standard X-ray imaging and was significantly faster and less painful. Future prospective studies are required to confirm our findings.